2017
DOI: 10.2147/jpr.s138460
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in salivary markers of inflammation in response to experimental pain: does venipuncture matter?

Abstract: An important consideration in mechanistic research using biomarkers should include the use of saliva as an alternative to blood. The use of saliva would allow the study of susceptible populations such as older adults where venipuncture may not be feasible. Although saliva has been most commonly used to measure cortisol and tumor necrosis factor-α (TNFα), there is limited evidence that other cytokines found in saliva significantly change in response to laboratory-induced pain. Therefore, the aim of the current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…Whereas a recent study has suggested marginal differences in several inflammatory cytokines between young and elderly participants. In our study however, age could not further be examined because of the limited age-interval 28 . Nevertheless, we could demonstrate a significant association between stimulation of salivary flow and NGF expression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Whereas a recent study has suggested marginal differences in several inflammatory cytokines between young and elderly participants. In our study however, age could not further be examined because of the limited age-interval 28 . Nevertheless, we could demonstrate a significant association between stimulation of salivary flow and NGF expression.…”
Section: Discussionmentioning
confidence: 95%
“…Since it is not clear whether the menstrual cycle affects the salivary response and salivary flow we did not control for menstrual cycle variations. Further, according to some findings age may affects protein expression 35 but a recent study have shown negligible differences in inflammatory markers in young and elderly individuals 28 . A limited age interval was however used in the current study design to minimise a possible confounder.…”
Section: Discussionmentioning
confidence: 98%
“…Proteolytic bacteria such as Prevotella are known to degrade proteins and peptides and are associated with periodontitis [28,58]. It is known that the saliva composition changes with age due to the slower salivary flow [59], inadequate oral care, increase of several inflammatory mediators [60], systemic diseases and other additional environmental factors that together will affect the microbial composition in the saliva [28,61]. The adult salivary microbial population this cohort was more diverse including microbes like Streptococcus, Haemophilus, Rothia and Veillonella and Lautrophia, some are known to degrade carbohydrates [50].…”
Section: Discussionmentioning
confidence: 99%
“…Composition of human saliva depends both on systemic and local factors (Khan et al 2017 ). Thus, it may reflect pathophysiological processes relevant to the development both of systemic and local disease (Abdul Rehman et al 2017 ; Buczko et al 2015 ; Cruz-Almeida et al 2017 ). In this respect, saliva has been used as a diagnostic tool to aid the assessment of periodontal disease activity (Korte and Kinney 2016 ; Podzimek et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%